Polydopamine hydrophilic modification of polypropylene separator for lithium ion battery. Issue 15 (18th February 2014) - Wang, Dan; Zhao, Zhongling; Yu, Lina; Zhang, Kejin; Na, Hui; Ying, Shanqiang; Xu, Dechao; Zhang, Guo
ABSTRACT The modified polypropylene (PP) separators with self‐polymerization of dopamine on the surfaces are prepared by a simple solution‐immersion method to improve the interfacial hydrophilic and discharge performance. The contact angle test and the liquid electrolyte uptake capacity test results show that the wettability and the electrolyte‐retention ability of polydopamine‐modified separator are improved significantly. The robust and thin polydopamine layer on the surface also enhances thermal performance and tensile strength of the modified PP separator certified by DSC and tensile strength tests. The ionic conductivity of the modified PP separator is up to 3.08 mS·cm−1, ∼2.5 times of the bare separator. Good discharge capacity retention and C‐rate discharge performance are demonstrated by a 2025 coin half‐cell with the liquid electrolyte‐soaked polydopamine modified PP separator sandwiched between lithium metal anode and LiFePO4 cathode. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40543.